DESIGN AND MANUFACTURE OF BAMBOO HANDICRAFT DRYER MACHINE BASED ON LPG GAS - Muhammad Agus Saparudin; Rizal Justian Setiawan; Eko Budi; Aji Puspito; Imam Fauzi (Tadulako Science and Technology Journal, 2021)
Bamboo plant is one of Indonesia's natural resources. People use bamboo to make household furniture, fences, frames, and handicrafts. Bamboo plant is a special commodity that can be used as various kinds of handicraft products in DIY, precisely in Brajan area, Sleman Regency. Based on observations that have been conducted on one of the bamboo craftsmen in the Brajan area, bamboo handicraft is in great demand due to they have a unique and ethnic appearance, but the production process is quite complicated and takes a long time. According to the literature, this is due to bamboo plants are classified as herbaceous plants, namely plants with watery or wet stems. So far, the method used is drying bamboo handicrafts under the hot sun, and using a dryer that can only be used for one type of handicraft. This method is not optimal and not effective for producing bamboo handicrafts. Therefore, it is necessary to apply appropriate technology to optimize the production of bamboo crafts, the solution is to manufacture bamboo dryers to facilitate bamboo handicraft producers in the bamboo drying process. In general, the appearance of this tool resembles a cupboard. This tool has a size of 1200x800x1800 mm with three chambers. This tool works by utilizing the heat from the LPG gas stove. As a temperature controller, this tool is equipped with a blower that has been programmed with Arduino Uno and functions to stabilize the temperature if the heat generated exceeds the maximum limit. The dryer machine can dry bamboo handicrafts to a water content of 2.5% in just 40 minutes, very efficient compared to conventional methods. This tool can facilitate and optimize the production of bamboo handicrafts in the ​​Brajan area, Sleman, Special Region of Yogyakarta.